New 1, 4‐Dihydropyridines Down‐regulate Nitric Oxide in Animals with Streptozotocin‐induced Diabetes Mellitus and Protect Deoxyribonucleic Acid against Peroxynitrite Action. Issue 1 (25th January 2016) - Leonova, Elina; Sokolovska, Jelizaveta; Boucher, Jean‐Luc; Isajevs, Sergejs; Rostoka, Evita; Baumane, Larisa; Sjakste, Tatjana; Sjakste, Nikolajs
Abstract: Diabetes mellitus (DM) and its complications cause numerous health and social problems throughout the world. Pathogenic actions of nitric oxide (NO) are responsible to a large extent for development of complications of DM. Search for compounds regulating NO production in patients with DM is thus important for the development of pharmacological drugs. Dihydropyridines (1, 4‐DHPs) are prospective compounds from this point of view. The goals of this study were to study the in vivo effects of new DHPs on NO and reactive nitrogen and oxygen species production in a streptozotocin (STZ)‐induced model of DM in rats and to study their ability to protect DNA against nocive action of peroxynitrite. STZ‐induced diabetes caused an increase in NO production in the liver, kidneys, blood and muscles, but a decrease in NO in adipose tissue of STZ‐treated animals. Cerebrocrast treatment was followed by normalization of NO production in the liver, kidneys and blood. Two other DHPs, etaftorone and fenoftorone, were effective in decreasing NO production in kidneys, blood and muscles of diabetic animals. Furthermore, inhibitors of nitric oxide synthase (NOS) and an inhibitor of xanthine oxidoreductase (XOR) decreased NO production in kidneys of diabetic animals. Treatment with etaftorone decreased expression of inducible NOS and XOR in kidneys, whereas it increased the expression of endothelial NOS. In vitro, the studied DHPs did not significantly inhibit the activities of NOS and XOR but affected the reactivity of peroxynitrite with DNA. These new DHPs thus appear of strong interest for treatment of DM complications.